HUBUNGAN POLA ASUH IBU DENGAN KEMANDIRIAN ANAK USIA PRA SEKOLAH DI TAMAN KANAK-KANAK KUNTUM CERIA AMBON - Jacomina Anthonete Salakory; Kariyadi Kariyadi; Adolfina Bumbungan (Poltekkes Kemenkes Maluku, 2019)
Parenting mother is the ability of the mother to provide a time, concern and support against a child in order to be with the optimum growth and development, both physically, mentally, and social. The purpose of this research is to find out on parenting mother with independence of the pre-school age children in Taman Kanak-Kanak Kuntum Ceria Ambon. The kind of this study is correlational analytic research by using approach to cross sectional study. The samples as much as 77 of the respondents comprising the mother and child the age of a preschool, using a method total sampling. Collecting data obtained from charging questionnaires with the number of statement as much as 16 items. And the sheet observations a total of 15 items. The processing data to test Chi-square. Obtained a picture of parenting applied by the pre-school age in Taman Kanak-Kanak Kuntum Ceria Ambon most is parenting democratic. The level of independence children aged Midwestern obtained a picture that 87.7%f the child has been independent. Test results statistic Chi-square obtained value p= 0,865 means that there is no relationship parenting mother with the independence of the child. It is recommended to further research in order to be done the research against other variable that influence the independence of the child.